Experimental Study on the Creep Behaviour of Cemented Sand and Gravel (CSG) and Temperature Stress Prediction of CSG Dam under Seasonal Temperature Change - Xin Cai; Minmin Jiang; Xingwen Guo; Jiaojiao Chen; Qian Zhao (Advances in Civil Engineering)
Creep generally showed a great impact on the temperature stress of concrete structure. At present, little research has been done on the creep law of cemented sand and gravel (CSG), and the calculation of creep temperature stress mainly adopts a set of relevant parameters. In this context, experimental compressive creep tests were carried out on the specimens of large-sized cylinders with different cementing agent contents; the creep temperature stress of CSG was also calculated. The results showed that the creep of CSG increased with the increase of cementing agent content, but the specific creep was not obvious. In addition, the creep model of CSG with high accuracy was also obtained, which could provide a basis for the numerical simulation of CSG dam. Furthermore, the results of numerical simulation showed that creep has a great influence on the stress of CSG dam, and the thermal stress energy was less than 37%. At the same time, it was necessary to determine whether temperature control should be considered according to different cementing agent content and external climate conditions, which cannot be generalized.